In Harm's Way: Family Separation, Immigration Enforcement Programs and Security on the US-Mexico Border. (June 2015) - Slack, Jeremy; Martínez, Daniel E.; Whiteford, Scott; Peiffer, Emily
The Consequence Delivery System (CDS) is a suite of border and immigration enforcement programs designed to increase the penalties associated with unauthorized migration in order to convince people not to return (Rosenblum 2013). Despite its inauguration in 2011, many aspects of the CDS are not new. CDS does however, mark a shift from the deterrent strategy that, in the 1990s that relied heavily on the dangers of the natural terrain to dissuade unauthorized border crossers, to one that actively punishes, incarcerates, and criminalizes them. This article presents findings from the Migrant Border Crossing Study, a random sample survey of 1, 100 recently deported migrants in six cities in Mexico conducted between 2009 and 2012. It examines the demographics and family ties of deportees, their experiences with immigration enforcement practices and programs under the CDS, and how these programs have reshaped contemporary migration and deportation along the US-Mexico border. The article covers programs such as criminal prosecutions of illegal entries under Operation Streamline, and the Alien Transfer and Exit Program (ATEP) or lateral repatriation program which returns immigrants to different locations from where they illegally entered. In relationship to these programs, it considers issues of due process and treatment of deportees in US custody. It also examines interior enforcement under Secure Communities, which, during the study period, comprised part of the overarching border security plan, and screened virtually everybody arrested in the United States against immigration databases. The article concludes that these programs do not have a strong deterrent effect. Instead, immigration enforcement has led to a "caging effect" over the past two decades which has disrupted seasonal migration flows, increased familial and social ties to the United States, and decreased the probability of returning to Mexico once in the United States. The development of strong family and other ties to the United States contributes to a greater resolve to return post-deportation.